The New Old Rat ( Rattus , Mammalia) From Turkestan: Revisiting From a Genomics Perspective - Lissovsky, A. A.; Liu, N.; Obolenskaya, E. V.; Ivanova, E. A.; Ge, D. Y. (Zoologica scripta, 2025)
The Turkestan rat ( Rattus turkestanicus ) has long been classified as a part of the Himalayan rat R. pyctoris . In this study, we integrate genomic and morphological data to re‐evaluate the taxonomic status of this species. Morphological analyses indicate minimal differentiation between samples from the Himalayas and Turkestan, whereas significant genetic divergence is evident in both mitochondrial DNA and across whole‐genome SNPs. Genetic distance analysis of 13 mitochondrial protein‐coding sequences and population differentiation statistics (fixation index Fst) of genome‐wide SNPs also supported the divergence. Based on these findings, we propose reinstating R. turkestanicus as a full species.